Optical Switching in Next Generation Data Centers - Testa, Francesco; Pavesi, Lorenzo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book introduces the reader to the optical switching technology for its application to data centers. In addition, it takes a picture of the status of the technology and system architecture evolution and of the research in the area of optical switching in data center. The book is organized in four parts: the first part is focused on the system aspects of optical switching in intra-data center networking, the second part is dedicated to describing the recently demonstrated optical switching networks, the third part deals with the latest technologies developed to enable optical switching and, finally, the fourth part of the book outlines the future prospects and trends.
Part 1. System aspects of intra data center networking -- Chapter 1.Photonics Data Centers -- Chapter 2.Optical switching in Data Centers Architectures based on optical circuit switching -- Chapter 3.Optical switching in Data Centers: Architectures based on optical packet/burst switching -- Part 2. Demonstrations of optical switching in Data Center -- Chapter 4.OSA an Optical Switching Architecture for Data Center Networks with Unprecendented Flexibility -- Chapter 5. The Hi-Ring Architecture for Data Center Networks -- Chapter 6.Low Latency Interconnect Optical Network Switch (LIONS) -- Chapter 7. Torus-Topology Data Center Networks with Hybrid Opto-electronic Routers -- Chapter 8.LIGHTNESS: All-Optical SDN-enabled Intra-DCN with Optical Circuit and Packet Switching -- Chapter 9.Hybrid OPS/EPS Photonic Ethernet Switch and Pure Photonic Packet Switch -- Chapter 10. OPMDC: Optical Pyramid Data Center Network -- Part 3. Technologies for Optical Switching in Data Centers -- Chapter 11.Commercial optical switches -- Chapter 12.Silicon Photonics switch Matrices: Technologies and Architectures -- Chapter 13.Trends in High Speed Interconnects for Datacenter Networking: Multidimensional Formats and Their Enabling DSP -- Chapter 14.Trends in high speed interconnects for data center networking : InP monolithic integration -- Part 4. Prospects and future trends._Chapter 15. The future of switching in data centers.
Keywords: Telecommunication; Signal processing; Computer networks .; Application software; Electric power production; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Signal, Speech and Image Processing .; Computer Communication Networks; Computer and Information Systems Applications; Electrical Power Engineering